2012
DOI: 10.1016/j.ajpath.2011.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Molecular Profiling Reveals Asparagine Synthetase Is a Target in Castration-Resistant Prostate Cancer

Abstract: The identification of new and effective therapeutic targets for the lethal, castration-resistant stage of prostate cancer (CRPC) has been challenging because of both the paucity of adequate frozen tissues and a lack of integrated molecular analysis. Therefore, in this study, we performed a genome-wide analysis of DNA copy number alterations from 34 unique surgical CRPC specimens and 5 xenografts, with matched transcriptomic profiling of 25 specimens. An integrated analysis of these data revealed that the aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
3
50
0
Order By: Relevance
“…The IC50 values for enzyme confirmed the most potent Several plant species having disease preventive and therapeutic properties. This observation is of particular importance in many vegetables and fruits and the association of vegetable and fruit consumption with reduced cancer risk has been reported [32,56,72,73]. The present results indicate that L-asparaginase produced in the present study may serve as a natural chemotherapy target for the treatment of colon and HCC.…”
Section: Cytotoxicity and Anticancer Activity Ofl-aspargenasementioning
confidence: 53%
“…The IC50 values for enzyme confirmed the most potent Several plant species having disease preventive and therapeutic properties. This observation is of particular importance in many vegetables and fruits and the association of vegetable and fruit consumption with reduced cancer risk has been reported [32,56,72,73]. The present results indicate that L-asparaginase produced in the present study may serve as a natural chemotherapy target for the treatment of colon and HCC.…”
Section: Cytotoxicity and Anticancer Activity Ofl-aspargenasementioning
confidence: 53%
“…OIP5 (Opa interacting protein 5) is a cancer testis antigen and has been reported in other cancer types as a type of tumor‐associated antigen (TAA) (Tarnowski et al ., 2016); its detection in PC here suggests OIP5 being a TAA for PC. The remaining four genes VAV2 (VAV guanine nucleotide exchange factor 2), ASNS (asparagine synthesis), DNMT3B (DNA methyltransferase 3 beta), and AURKA (Aurora kinase A) not only all promote PC pathogenesis but also play a role in the development of CRPC (Gravina et al ., 2011; Magani et al ., 2017; Mosquera et al ., 2013; Sircar et al ., 2012). VAV2 is a coactivator of androgen receptor (AR) and sustains AR signaling under androgen deprivation therapy (ADT) (Magani et al ., 2017); it also promotes angiogenesis and metastasis (Barrio‐Real and Kazanietz, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the TCGA cohort had 10 total mortality, it is intriguing that 8 of these 10 deaths occurred in patients with SigMuc1NW‐positive PC (Fig. 2B, P  = 0.00212), which are consistent with VAV2, ASNS, DNMT3B, and AURKA being factors promoting CRPC development (Gravina et al ., 2011; Magani et al ., 2017; Mosquera et al ., 2013; Sircar et al ., 2012). As expected, SigMuc1NW displays an overlapping pattern with the 9‐gene genomic signature used to select DEGs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one study also showed that the enhanced expression of ASNS protected pancreatic cancer cells from apoptosis induced by glucose deprivation and cisplatin (18). Recently, some studies found that ASNS is overexpressed in castration-resistant prostate cancer (CRPC) and that depletion of asparagine using ASNS inhibitors may be a novel strategy for targeting CRPC cells (19). Another study showed that the expression of ASNS was an independent factor affecting the survival of HCC patients, and low ASNS expression in HCC was correlated with worse surgical outcomes (20).…”
Section: Introductionmentioning
confidence: 99%